Enzymatic synthesis of 1,2-aminocyclopentanols and 1,2-diaminocyclopentanes - Kolodiazhna, A.O.; Veriovka, O.V.; Kolodiazhnyi, O.I. (Reports of the National Academy of Sciences of Ukraine, 2019)
Optically active 1,2-aminocycloalkanols and 1,2-diaminocycloalkanes are components of many biologically active natural compounds, being important pharmacophore groups. In the present work, the resolution of racemates into enantiomers, by using enzymes to obtain the abovementioned compounds of high optical purity, is proposed. Burkholderia cepacia lipase was used to separate (±)-cis-2-aminocyclopentanol. Cyclopentane epoxide was used as a starting compound, which was converted into racemic aminocyclopentanol with aqueous ammonia. The amino group of the racemic compound was then protected by the tertbutyloxycarbonyl group by the treatment with ditertbutyl dicarbamate in the presence of triethylamine. Both enantiomers of transaminocyclopentanol with high optical yield were obtained. The resulting aminocyclopentanol was converted into a mesylate by the reaction with mesyl chloride. Azidaminocyclopentane was obtained by the subsequent reaction of mesylate with sodium azide in DMF upon the heating to 80 °C. The reaction was accompanied by the inversion of the absolute configuration with the formation of a product having the (S,R)-absolute configuration. As a result, optically pure 1,2-cis( S,R)-azidaminocyclopentane was obtained. The hydrogenation of the azide using a PtO2 catalyst and the subsequent protection of the amine group by a tertbutoxycarbonyl group resulted in the formation of vicinal diaminocyclopentane. The absolute configuration of compounds was established by the Kazlauskas method. The structure of the compounds was confirmed by NMR and chromatographymass spectrometry.